Impact of High-Power Short-Duration Radiofrequency Ablation on Esophageal Temperature Dynamic. (November 2021) - Yavin, Hagai D.; Bubar, Zachary P.; Higuchi, Koji; Sroubek, Jakub; Kanj, Mohamed; Cantillon, Daniel; Saliba, Walid I.; Tarakji, Khaldoun G.; Hussein, Ayman A.; Wazni, Oussama; Anter, Elad
Abstract : Background: High-power short-duration (HP-SD) radiofrequency ablation (RFA) has been proposed as a method for producing rapid and effective lesions for pulmonary vein isolation. The underlying hypothesis assumes an increased resistive heating phase and decreased conductive heating phase, potentially reducing the risk for esophageal thermal injury. The objective of this study was to compare the esophageal temperature dynamic profile between HP-SD and moderate-power moderate-duration (MP-MD) RFA ablation strategies. Methods: In patients undergoing pulmonary vein isolation, RFA juxtaposed to the esophagus was delivered in an alternate sequence of HP-SD (50 W, 8–10 s) and MP-MD (25 W, 15–20 s) between adjacent applications (distance, ⩽4 mm). Esophageal temperature was recorded using a multisensor probe (CIRCA S-CATH). Temperature data included magnitude of temperature rise, maximal temperature, time to maximal temperature, and time return to baseline. In swine, a similar experimental design compared the effect of HP-SD and MP-MD on patterns of esophageal injury. Results: In 20 patients (68.9±5.8 years old; 60% persistent atrial fibrillation), 55 paired HP-SD and MP-MD applications were analyzed. The esophageal temperature dynamic profile was similar between HP-SD and MP-MD ablation strategies. Specifically, the magnitude of temperature rise (2.1 °C [1.4–3] versus 2.0 °C [1.5–3]; P =0.22), maximal temperature (38.4 °C [37.8–39.3] versus 38.5 °C [37.9–39.4]; P =0.17), time to maximal temperature (24.9±7.5 versus 26.3±6.8 s; P =0.1), and time of temperature to return to baseline (110±23.2 versus 111±25.1 s; P =0.86) were similar between HP-SD and MP-MD ablation strategies. In 6 swine, esophageal injury was qualitatively similar between HP-SD and MP-MD strategies. Conclusions: Esophageal temperature dynamics are similar between HP-SD and MP-MD RFA strategies and result in comparable esophageal tissue injury. Therefore, when using a HP-SD RFA strategy, the shorter application duration should not prompt shorter intervals between applications.